A dangerous place [compact disc, unabridged] - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel, 2015)
In Spring 1937, stopping in Gibraltar on her journey home to England, Maisie Dobbs is drawn into the investigation of the murder of Sebastian Babayoff, a photographer and member of Gibraltar's Sephardic Jewish community.